2014
DOI: 10.1074/jbc.m114.609552
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structural Analysis of an l-Asparaginase Enzyme from Guinea Pig with Putative Tumor Cell Killing Properties

Abstract: Background: Guinea pig serum and liver contain an enzyme with L-asparaginase activity. Results: H0W0T5_CAVPO (gpASNase1) displays a low micromolar K m with Asn. Structures of apo and ASP complex are presented. Conclusion: gpASNase1is the likely identity of a guinea pig L-asparaginase endowed with anticancer properties. Significance: The high sequence identity to the human enzymes and its lack of L-glutaminase activity make gpASNase1 a potential replacement for the bacterial enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 40 publications
1
73
0
9
Order By: Relevance
“…Gene Cloning and Mutagenesis-A codon-optimized synthetic gene corresponding to the amino acid sequence of ErA (UniProt entry P06608) lacking the first 21-amino acid signal peptide was synthesized by Genscript as described earlier (29). The synthetic gene was digested with NdeI and BamHI-HF restriction enzymes, gel-purified, and ligated into a His 6 -SUMOpET14b vector (where the His 6 tag is followed by the yeast protein SUMO (small ubiquitin modifier, Smt3p) using Instant Sticky End DNA ligase (New England BioLabs), generating the His 6 -SUMO-pET14b-ErA-WT plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene Cloning and Mutagenesis-A codon-optimized synthetic gene corresponding to the amino acid sequence of ErA (UniProt entry P06608) lacking the first 21-amino acid signal peptide was synthesized by Genscript as described earlier (29). The synthetic gene was digested with NdeI and BamHI-HF restriction enzymes, gel-purified, and ligated into a His 6 -SUMOpET14b vector (where the His 6 tag is followed by the yeast protein SUMO (small ubiquitin modifier, Smt3p) using Instant Sticky End DNA ligase (New England BioLabs), generating the His 6 -SUMO-pET14b-ErA-WT plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Protein Expression and Purification-Protein expression and purification were performed as previously described (29). In brief, plasmids corresponding to wild-type ErA (ErA-WT) or the mutant constructs (verified by sequencing) were transformed into E. coli BL21(DE3) C41 cells for expression.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported the first structural characterization of a mammalian type I/II L-asparaginase, that from the guinea pig (5). By sequence homology, this guinea pig L-asparaginase would be classified as a type I enzyme; therefore we refer to it as gpASNase1.…”
mentioning
confidence: 99%
“…Furthermore, treatment efficacy can be greatly compromised upon the development of antibodies, which inactivate and deplete the enzyme. Because gpASNase1 is a mammalian L-asparaginase, it would be expected to have lower immunogenicity compared with the Food and Drug Administration-approved bacterial type II enzymes; therefore we suggested that the guinea pig enzyme would make a promising replacement for the bacterial enzymes (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation